Tinjauan Kualitatif Masalah Pembelajaran Fisika Selama Masa Pandemi COVID-19 - Disty, Adisty Anggraeni Putri B.Gobel; Haeruddin, Haeruddin (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2023)
This research aims to determine the problems of learning physics during the pandemic of COVID-19 at SMA Negeri Tolitoli. The design of the research is descriptive qualitative research with 27 subjects consisting of principals/vice principals, physics teachers and students at SMA Negeri Tolitoli. The techniques of data analysis in this reseacrh included three activities, namely data reduction, data presentation and conclusion drawing. The results show that there were various problems in learning physics at SMA Negeri Tolitoli, namely: (1) unstable internet connection and insufficient internet quota; (2) low IT mastery; (3) lack of mobile phones, as not everyone has it. The solution to minimize the problems faced is by doing offline learnig in stages or gathering students at an assembly point and then inviting the teacher to come to teach, using applications that don’t require a lot of internets, doing home visits/visiting student’s homes, making explanation videos so students can easily understand the material, contacting students who collected the assignments late and making it easier for students if students find it difficult about the assignments given. With this research, teachers are expected to find solutions easily when they encounter the same problem.